Gender Biased Elements In The "Interactive English" Textbooks For Junior High School Students In Grobogan Regency - Wahyuningsih, Dhita Tri, Drs. Djoko Srijono, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
Gender biased elements usually found in the textbooks. This research is aimed at (1) describing the kinds of gender biased elements that appear in "Interactive English" textbooks, (2) describing in what kinds of context of situations gender biased elements appear. The writer uses descriptive qualitative method in this research. The object analyzed are gender biased elements of "Interactive English" textbooks. The data of this research is conversations in the textbooks. The data source of this research is the "Interactive English" textbooks for Junior High School students. In collecting the data, the writer uses document. Having analyzed the data, the writer finds that (1) the kinds of gender biased elements are divided into three; women marginalization consists of role of marginalization and language marginalization, women subordination, and stereotypical element; (2) related to the describing in what kinds of context of situations, the writer find that gender biased element appear in informal.